A case of acute respiratory distress syndrome associated with novel H1N1 treated with intravenous immunoglobulin G - Jen, Lim Chong; Sapari, Satwi; Kuan, Yeh Chunn (Elsevier, 2011)
Influenza A “novel H1N1” with severe acute respiratory distress syndrome (ARDS) is a serious illness that poses a challenge to clinicians managing such cases. This case report reveals a patient with ARDS secondary to influenza A with deteriorating clinical status, who improved tremendously after intravenous immunoglobulin G (IV IgG). Patients with H1N1 associated with ARDS may be given a trial of IV IgG. More case reports and trials are required to ascertain the efficacy of IV IgG and the best dosage and timing of starting IV IgG in relation to antiviral therapy.